Cover and Table of Content - Journal of Mathematics Education, AlphaMath: (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2024)
FOREWORDAssalamu’alaikum Wr. Wb. Praise the presence of Allah SWT for all the overflow of His Rahmat so that we can publish the journal AlphaMath volume ten number two. The creation of the journal AlphaMath aims to develop a writing culture for educators, both teachers and lecturers. The AlphaMath journal also seeks to accommodate all forms of research in mathematics education. The production of this journal aligns with the goal and mission of the Department of Mathematics Education, Universitas Muhammadiyah Purwokerto.The overall content of this journal discusses mathematics education. This is done to encourage educators to innovate in their teaching and share their ideas with others. Hopefully, this journal will be assessed continuously to improve its quality. The current version of AlphaMath contains articles on ethnomathematics, learning models, mathematics skills, literacy and numeracy. All articles in this edition (11 research articles) include 39 authors from 2 countries of origin (Albania and Indonesia)Hopefully, this AlphaMath journal can provide benefits for readers and educational actors.Wassalamu’alaikum Wr. Wb.